A Multicenter Study to Optimize Carbapenem Use. (4th October 2017) - Sherman, Amy; Palaco, Federico; Goolsby, Tiffany; Jacob, Jesse; Pack, Jan; Johnson-Martinez, Krysta; Wong, Jordan; Sexton, Mary-Elizabeth; Frew, Paula; Fridkin, Scott; Kandiah, Sheetal; Fenimore, Vincent; et al.
Abstract: Background: Infection with carbapenem-resistant bacteria has become a major threat. Effective stewardship of antibiotics, particularly carbapenems, remains essential to control carbapenem-resistant bacteria. We attempted to determine the appropriateness of carbapenem use so that interventions to optimize carbapenem use can be specificly formulated. Methods: We developed criteria for appropriate, suboptimal, and inappropriate carbapenem use for empiric carbapenem use and non-empiric (after 48–72 hours with microbiology available culture results) carbapenem use. We conducted a multi-center, retrospective review across three of Emory-affiliated hospitals: the Atlanta Veterans Hospital (173 beds), Emory University Hospital (573 beds), and Emory University Midtown Hospital (511 beds). We reviewed 211 charts between July, 2015 and December 2015. The charts were randomly selected from patients >21 years old who were administered a carbapenem for more than 24h. We determined which carbapenem was used; patient location (ICU vs. floor); any patient history of multi-drug resistant organisms; infection site; allergy history; and whether Infectious Disease consultation was obtained. One person (A.S.) reviewed all 211 charts for appropriateness of carbapenem use. Results: Of 211 cases, we classified 76% as appropriate use, 21% as suboptimal, and 3% as inappropriate. The most commonly identified reasons for suboptimal use were suspected severe intra-abdominal sepsis and limb or life-threatening soft-tissue infections in which other, more narrow-spectrum formulary antibiotics were available for use. Four of six cases of inappropriate use occurred in the setting of β-lactam allergy. For non-empiric carbapenem use, while we classified 69.7% (147/211) of use as appropriate, microbiology cultures were unrevealing in 19.9% (42/211) of cases. Cultures grew an organism necessitating carbapenem therapy in only 24% (51/211) of cases. Conclusion: Interventions to optimize carbapenem use should focus on clinical scenarios that commonly lead to suboptimal or inappropriate use. The frequency of unrevealing microbiology cultures suggests that more sensitive microbiologic techniques to determine causative agents may help to decrease carbapenem use. Disclosures: S. Fridkin, Pfizer: Consultant and Grant Investigator, Consulting fee and Research support